2015
DOI: 10.1159/000368324
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Elderly Kidney Transplant Recipients from Spousal Donors

Abstract: Introduction: Patients aged 60 years and older stand for the fastest growing group of patients with end-stage renal disease worldwide, and the need for kidney transplants among this population is rising. In Japan, living donor kidney transplantation is mainly performed to deal with the severe shortage of deceased donors, and the number of spousal transplants is currently increasing. Patients and Methods: A total of 164 patients with ESRD underwent living donor kidney transplantation at our institution, of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Because of the differences in the hereditary background of the spouses, the rate of ABO-incompatibility and the number of HLA mismatches in living kidney transplantation between spouses are greater than those in living-related kidney transplantation. There are several published reports giving a higher incidence of acute rejection in kidney transplantation between spouses because of poor histocompatibility [9,10]. Our results suggested that ABO-incompatible kidney transplantation between spouses could be a high-risk procedure due to ABO-incompatibility and poor histocompatibility.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Because of the differences in the hereditary background of the spouses, the rate of ABO-incompatibility and the number of HLA mismatches in living kidney transplantation between spouses are greater than those in living-related kidney transplantation. There are several published reports giving a higher incidence of acute rejection in kidney transplantation between spouses because of poor histocompatibility [9,10]. Our results suggested that ABO-incompatible kidney transplantation between spouses could be a high-risk procedure due to ABO-incompatibility and poor histocompatibility.…”
Section: Discussionsupporting
confidence: 57%
“…Spouses currently occupy the greatest source of living donor kidneys in Japan, but there could be a high rate of acute rejection because of low histocompatibility [9,10]. However, there are no available reports on spousal ABO-incompatible kidney transplantation using rituximab.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we had no incidence of post-transplant rejection and no need for preoperative immunosuppressive measures. However, living donor transplant is increasing among adults with ESRD aged 60 and older, and spousal transplantation is also increasing due to limited numbers of deceased donors [24]. Age-related immune dysfunction may increase immunological risk in spousal transplants due to ABO incompatibility and/or poor histocompatibility, and immunosuppressive treatment may also increase risk of infection and malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related immune dysfunction may increase immunological risk in spousal transplants due to ABO incompatibility and/or poor histocompatibility, and immunosuppressive treatment may also increase risk of infection and malignancies. To offset these risks, Iwai et al [24] applied desensitization protocols so that elderly patients with spousal donors could undergo living donor transplant successfully despite ABO incompatibility or low histocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the number of patients with chronic kidney disease is partly due to demographic reasons [1,2]. In addition, waiting times are increasing due to a decrease in organ donations.…”
Section: Introductionmentioning
confidence: 99%